Clinical presentation and serological diagnosis of syphilis reinfection in men living with HIV: a retrospective cohort study. (2nd September 2021) - Mischler-Gornostaeva, Ksenia; Glatz, Martin; Fehr, Jan; Bosshard, Philipp Peter
Abstract : Objectives: Studies on the characteristics of syphilis reinfection are scarce despite increasing numbers and proportions of cases. We aimed to gain insights into the clinical and serological presentation of reinfected men living with HIV and to evaluate diagnostic criteria for syphilis reinfection. Methods: We conducted a retrospective cohort study of 259 HIV-positive men diagnosed with syphilis between January 1999 and September 2015 at the University Hospital Zurich. We compared patients with a single syphilis infection (n = 109) to patients with reinfections (n = 150). Results: The two groups matched in age, sexual orientation and numbers of other STIs. Reinfected patients more often presented with latent syphilis than patients with a single syphilis episode (41.9% vs 8.9%; p<0.001). Although generally high venereal diseases research laboratory (VDRL) or rapid plasma reagin (RPR) titres (median 1:32) were seen in reinfected patients, 19.4% had titres ≤1:8. Treponema pallidum passive particle agglutination (TPPA) titres were significantly higher (1:81 840 vs 1:10 240; p<0.001), while IgM values were significantly lower (1.27 vs 3.5; p<0.001) in syphilis reinfections than in first infections. The TPPA increased ≥fourfold in >92.3% of reinfected patients. Conclusions: Our data highlight the paramount importance of regularly screening patients at risk as syphilis reinfections in men living with HIV are more likely to be latent infections, that is, without symptoms. As non-treponemal tests might be biologically false-positive (up to a titre of 1:8) due to various conditions, a ≥fourfold increase of the TPPA might be considered as optional criterion for the diagnosis of syphilis reinfections. This could be especially valuable for diagnosing reinfected latent stage patients.